The constitutional framework for enhanced cooperation in EU law - Böttner, Robert (Koninklijke Brill NV, 2021)
Introduction -- Flexibility in the logic of European integration -- Practice of enhanced cooperation -- The authorisation phase of enhanced cooperation -- The implementing phase of enhanced cooperation -- Accession to, withdrawal from, and termination of an established cooperation -- Judicial review in enhanced cooperation -- Other forms of closer cooperation in Union law -- Conclusions and prospects
Includes bibliographical references and index